Implementation of GAG Based on ZCP in Enhancing Economic Empowerment of Communities in West Sulawesi - Rufaida, Erty Rospyana; Ilyas, Herlina (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study aims to examine the implementation of Good Amil Governance (GAG) principles based on Zakat Core Principles (ZCP) within zakat management institutions in three regencies with the highest poverty rates in West Sulawesi: Polewali Mandar, Majene, and Mamasa. The main issue addressed is how professional, transparent, and accountable zakat governance can support the economic empowerment of mustahik communities. This research adopts the position that implementing GAG based on ZCP is a strategic approach to improving the effectiveness of zakat management, which has not been comprehensively studied at the regency level. A qualitative method using a case study approach and Participatory Action Research was employed through in-depth interviews, observations, and analysis of official documents. The findings indicate that although the fundamental principles of zakat governance have been applied, there are weaknesses such as suboptimal public transparency, underperforming internal audit functions, limited digitalization, and empowerment program effectiveness that is not yet integrated with ongoing training and monitoring. This study contributes by expanding the application of Good Amil Governance principles based on the Zakat Core Principles at the district level, which has previously been rarely examined. The study also identifies various gaps in zakat governance, such as low public transparency, weak internal audit functions, and limited digitalization. [Penelitian ini bertujuan mengkaji penerapan prinsip Good Amil Governance (GAG) berbasis Zakat Core Principles (ZCP) pada lembaga pengelola zakat di tiga kabupaten dengan tingkat kemiskinan tertinggi di Sulawesi Barat, yaitu Polewali Mandar, Majene, dan Mamasa. Isu utama yang dibahas adalah bagaimana tata kelola zakat yang profesional, transparan, dan akuntabel dapat mendukung pemberdayaan ekonomi masyarakat mustahik. Penelitian ini mengambil posisi bahwa implementasi GAG berbasis ZCP merupakan pendekatan strategis untuk meningkatkan efektivitas pengelolaan zakat yang belum banyak dikaji secara komprehensif di tingkat kabupaten. Metode kualitatif dengan pendekatan studi kasus dan Participatory Action Research digunakan melalui wawancara mendalam, observasi, dan analisis dokumen resmi. Hasil penelitian menunjukkan bahwa meskipun prinsip dasar tata kelola zakat telah diterapkan, terdapat kelemahan seperti kurang optimalnya transparansi publik, fungsi audit internal yang belum berjalan maksimal, keterbatasan digitalisasi, serta efektivitas program pemberdayaan yang belum terintegrasi dengan pelatihan dan monitoring berkelanjutan. Penelitian ini memberikan kontribusi dengan memperluas penerapan prinsip Good Amil Governance berbasis Zakat Core Principles pada level kabupaten yang sebelumnya jarang dikaji. Penelitian ini juga mengidentifikasi berbagai kesenjangan dalam tata kelola zakat, seperti rendahnya transparansi publik, lemahnya fungsi audit internal, dan terbatasnya digitalisasi.]